A Review Paper for Hotel Management System Application Using Android - Prashant, Bhandare; Shrimant, Chavan Kshitij; Keshav, Gaikwad Prashant; Suraj, Patil Varad; Hanumant, Shelke Prathmesh (International Journal of Computer Sciences and Engineering, 2024)
The Android HMS Application aims at streamlining hospitality industry operations by uplifting the guest experience through a smarter solution of managing a hotel. In this application, it provides all-inclusive solutions for managing a hotel or managing reservations, check-in, check-out, and billing of guests on mobile devices. The feature of real-time room availability and booking makes it easier for guests to book room reservations, thereby assisting in total customer satisfaction. All modules like guest information management, room assignment management, and payment processing are included in the application of HMS in a very user-friendly manner so that guests as well as the hotel staff use the application easily. Advanced features include automated notifications, feedback collection, and reporting tools that allow the management to make informed decisions based on data analytics. Another feature the application offers is multi-language support. This means that it supports those clients who speak different languages. With its security, the users` data will be safe, hence allowing the user to enjoy full confidence. The use of Android technology by this Hotel Management System efficiently runs the operations of the hotel while raising the standards of the guests` experience, therefore positioning such a hotel to compete with other hotels in the market.